The Role of Occlusal Adjustment on Treatment of Tooth’s Mobility: Case Report - Cut Ati Ningsih; Irma Ervina; Aini Hariyani Nasution (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2024)
Introduction: Periodontal disease and traumatic occlusion can result in loss of alveolar bone so that the teeth become mobile. Treatment of tooth’s mobility depends on the etiology and prognosis of the tooth. Case: This case report describes the treatment of a tooth’s mobility due to periodontal disease and traumatic occlusion. The first case was a 39-year-old female patient with complaints of mobility of teeth, the gums of the lower front teeth were often swollen, pus intermittently since 2 years ago. Clinical examination showed tooth 41 mobility grade 2 with a pocket depth of 6 mm and teeth 31,32,42 mobility grade 1 with a pocket depth of 3 mm and were traumatic occlusion on teeth 11,21 and 41. Radiographic showed infrabony defects of teeth 31 and 41 with 30% bone loss. The second case was a 22-year-old female patient with complaints of bleeding gums when brushing her teeth and mobility of lower front teeth since 1 year ago. Clinical examination showed teeth 31,41 mobility grade 2 with a pocket depth of 4 mm and 6 mm, teeth 32,42 mobility grade 1 with a pocket depth of 3 mm, there was traumatic occlusion on teeth 21 and 31. Radiographic showed suprabony defects on teeth 31 and 41 with 30% bone loss. Case Management: In both cases, initial treatment was carried out with scaling and root planing, followed by occlusal adjustment. One week post-treatment oclusal adjustment there was no tooth mobility in either case. Discussions: Mobility can be caused by periodontal tissue inflammation, alveolar bone destruction, and traumatic occlusion. Conclusion: Occlusal adjustment can reduce mobility in traumatic occlusal teeth.